The Relationship between Leadership Styles and Employee Engagement: Evidences from Construction Companies in Malaysia - Liu, Yao; Kee, Shin Woan; Mohd Hanafiah, Ahmad (2015)
The growing global economy has intensified the complexity of the discrete but interrelated tasks involved in construction project. In order to achieve project success, the interactions between the team leaders and followers are vital. Taking into consideration the importance of leader to the organization, this study is therefore to examine the relationship between leadership styles (i.e. autocratic, democratic and laissez-faire) and employee engagement among the construction industry in Malaysia. Forty (40) sets of questionnaires were collected from the companies registered under the Construction Industry Development Board (CIDB) Grade 7, located in Kuantan, Malaysia. The study reveals that the democratic leadership style is more frequently practiced by practitioners than the other two coexisting leadership styles, autocratic and laissez-faire. The level of employee engagement in the construction industry shows frequently high. And the three leadership styles are positively and significantly associated with employee engagement; but still the democratic leadership style demonstrates stronger association with the employee engagement. Hence, in order to ensure employees more vigorous, dedicated as well as absorbed in their work, project leaders are suggested to be more trustable, honest, fair and communicative towards their followers.